Mediated catalysis of Paracoccus pantotrophus cytochrome c peroxidase by P. pantotrophus pseudoazurin: kinetics of intermolecular electron transfer - Sousa, P. M. Paes de (2007)
J Biol Inorg Chem (2007) 12:691–698 DOI 10.1007/s00775-007-0219-9